CNS Metastases from Bone and Soft Tissue Sarcomas in Children, Adolescents, and Young Adults: Are They Really So Rare?. (24th January 2017) - Bekiesinska-Figatowska, Monika; Duczkowska, Agnieszka; Duczkowski, Marek; Bragoszewska, Hanna; Romaniuk-Doroszewska, Anna; Iwanowska, Beata; Szkudlinska-Pawlak, Sylwia; Madzik, Jaroslaw; Bilska, Katarzyna; Raciborska, Anna
Abstract : Purpose . To check whether primary involvement of brain/spinal cord by bone/soft tissue sarcomas' metastases in children is as rare as described and to present various morphological forms of bone/soft tissue sarcomas' CNS metastases. Methods . Patients with first diagnosis in 1999–2014 treated at single center were included with whole course of disease evaluation. Brain/spinal canal magnetic resonance imaging (MRI)/computed tomography were performed in cases suspicious for CNS metastases. Extension from skull/vertebral column metastases was excluded. Results . 550 patients were included. MRI revealed CNS metastases in 19 patients (incidence 3.45%), 14 boys, aged 5–22 years. There were 12/250 osteosarcoma cases, 2/200 Ewing's sarcoma, 1/50 chondrosarcoma, 3/49 rhabdomyosarcoma (RMS), and 1/1 malignant mesenchymoma. There were 10 single metastases and 7 cases of multiple ones; in 2 RMS cases only leptomeningeal spread in brain and spinal cord was found. Calcified metastases were found in 3 patients and hemorrhagic in 4. In one RMS patient there were numerous solid, cystic, hemorrhagic lesions and leptomeningeal spread. Conclusions . CNS metastases are rare and late in children with bone/soft tissue sarcomas, although in our material more frequent (3.45%) than in other reports (0.7%). Hematogenous spread to brain and hemorrhagic and calcified lesions dominated in osteosarcoma. Ewing sarcoma tended to metastasize to skull bones. Soft tissue sarcomas presented various morphological forms.